Evalution of muscle strength and functionality of hospitalized neurological patients (Research, Society and Development, 2024)
Objective: To verify the correlation between respiratory and peripheral muscle strength and functionality in hospitalized neurological patients. Methods: This is a cross-sectional study, evaluating 22 neurological patients hospitalized in a Regional Hospital, where a questionnaire was applied to collect personal data, and respiratory muscle strength was evaluated using the Manovacuometer, peripheral muscle strength using the Medical Research Council (MRC) and the dynamometer, and used the Functional Independence Measurement (MIF) scale to assess functional independence. Data normality was verified using the Shapiro-Wilk test, data were expressed as median and interquartile range, frequency and percentage. Kendall's Tau B test was used for correlation analyses. The significance value adopted was p